Indigenous Studies: Tool of Empowerment Within the Academe - Herbert, Jeannie (The Australian Journal of Indigenous Education, 2010)
Abstract In this paper, I consider the importance of Indigenous studies programs, at both undergraduate and postgraduate levels, as critical elements in enabling Indigenous Australian students to engage in the academe in ways that not only allow them to empower themselves, but, ultimately, to become effective change agents within both their own and the wider Australian community. While this paper will highlight the challenges that Indigenous Australians face in their engagement within the university learning environment, it will also reveal the increasingly successful outcomes that are being achieved. A particular focus of the paper will be to acknowledge higher education as a tool of empowerment – a process that enables people to identify and address their own issues, and to use such knowledge and understanding as the platform for personal, positive growth. Finally this paper will contextualise higher education from within an Indigenous perspective to demonstrate how Indigenous studies not only contributes to the empowerment of the individual but also has a critical role in ultimately re-positioning Indigenous Australians in the wider Australian society.